If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + 6(x + -9) = 5 + -4(x + -8) Reorder the terms: 1 + 6(-9 + x) = 5 + -4(x + -8) 1 + (-9 * 6 + x * 6) = 5 + -4(x + -8) 1 + (-54 + 6x) = 5 + -4(x + -8) Combine like terms: 1 + -54 = -53 -53 + 6x = 5 + -4(x + -8) Reorder the terms: -53 + 6x = 5 + -4(-8 + x) -53 + 6x = 5 + (-8 * -4 + x * -4) -53 + 6x = 5 + (32 + -4x) Combine like terms: 5 + 32 = 37 -53 + 6x = 37 + -4x Solving -53 + 6x = 37 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -53 + 6x + 4x = 37 + -4x + 4x Combine like terms: 6x + 4x = 10x -53 + 10x = 37 + -4x + 4x Combine like terms: -4x + 4x = 0 -53 + 10x = 37 + 0 -53 + 10x = 37 Add '53' to each side of the equation. -53 + 53 + 10x = 37 + 53 Combine like terms: -53 + 53 = 0 0 + 10x = 37 + 53 10x = 37 + 53 Combine like terms: 37 + 53 = 90 10x = 90 Divide each side by '10'. x = 9 Simplifying x = 9
| 5x+35=10 | | 5(2b-5)+(6b+5)= | | fx=4x^2-8x-9 | | 52x+26= | | 4(6z-1)-4(z+8)=17(z+1) | | (-f-9)+(9x+2)= | | -0.1+8.56=-0.3x+2.36 | | -3t^2+18t-4=0 | | -7y-7=-6y-8 | | 11x-9=6x+36 | | 8/2y-10=-2 | | 3t^2+18t-4=0 | | 1073/2941=56.7/x | | 36=x-12 | | 3(x+2)+5(2x+1)=27 | | -x+6=-27 | | -10=17+x | | 3lox=3.3 | | 177=-y+65 | | -2x+5=-1x+1 | | 3logx=3.3 | | -1x+1=-12 | | 9/x=63/77 | | 5u+3=33 | | 19x+5y=7 | | 17p^2+16=2151 | | f(x)=x^3-1.5x^2-1 | | N/400=2/100 | | 13p^3-3=4209 | | x^(5/3)=1.10 | | 9(11-k)=3(3k-6) | | 4x^2-x+29=0 |